MYBPC1, an Emerging Myopathic Gene: What We Know and What We Need to Learn - Geist, Janelle; Kontrogianni-Konstantopoulos, Aikaterini (Frontiers in Physiology, 2016)
Myosin Binding Protein-C (MyBP-C) comprises a family of accessory proteins that includes the cardiac, slow skeletal, and fast skeletal isoforms. The three isoforms share structural and sequence homology, and localize at the C-zone of the sarcomeric A-band where they interact with thick and thin filaments to regulate the cycling of actomyosin crossbridges. The cardiac isoform, encoded by MYBPC3, has been extensively studied over the last several decades due to its high mutational rate in congenital hypertrophic and dilated cardiomyopathy. It is only recently, however, that the MYBPC1 gene encoding the slow skeletal isoform (sMyBP-C) has gained attention. Accordingly, during the last 5 years it has been shown that MYBPC1 undergoes extensive exon shuffling resulting in the generation of multiple slow variants, which are co-expressed in different combinations and amounts in both slow and fast skeletal muscles. The sMyBP-C variants are subjected to PKA- and PKC-mediated phosphorylation in constitutive and alternatively spliced sites. More importantly, missense, and nonsense mutations in MYBPC1 have been directly linked with the development of severe and lethal forms of distal arthrogryposis myopathy and muscle tremors. Currently, there is no mammalian animal model of sMyBP-C, but new technologies including CRISPR/Cas9 and xenografting of human biopsies into immunodeficient mice could provide unique ways to study the regulation and roles of sMyBP-C in health and disease.